Nmi protein interacts with regions that differ between MycN and Myc and is localized in the cytoplasm of neuroblastoma cells in contrast to nuclear MycN - Bannasch, Detlev; Wittke, Isabel; Schwab, Manfred (Oncogene, 1999)
Myc family proteins play an important role in cellular processes such as proliferation, differentiation, apoptosis and transformation. A number of interaction partners of Myc have been identified, such as Max, p107, TBP, YY1, Miz-1, AP-2 and Nmi. Both Max and Nmi also bind to MycN. In contrast to the well defined binding of Max to Myc family proteins the interaction of Nmi with Myc or MycN is only poorly characterized. By employing the yeast two-hybrid system we have mapped the regions of MycN and Myc responsible for binding to Nmi. For MycN exclusively a central region mediates binding to Nmi. In contrast, for Myc a C-terminal portion of the protein, and possibly also a central part, is involved in Nmi interaction. Nmi does not interact with Max and has no transactivation capabilities in yeast, suggesting that Nmi alone is not a transcriptional activator in mammalian cells. Immunofluorescence demonstrates that both in 293 embryonic kidney cells and in Kelly neuroblastoma cells all detectable ectopically expressed Nmi is localized in the cytoplasm, in part in a punctate, granular pattern. MycN, which is highly expressed in Kelly cells consequent to amplification, appears to be localized exclusively in the nuclei. This directly demonstrates that in the same cell at least the major proportion of MycN and Nmi is localized in different cellular compartments. This result is confirmed by the finding that endogenous Nmi, which is expressed in Kelly cells only after stimulation with interferon γ, is detected exclusively in the cytoplasm of these cells. Therefore only a very small amount of MycN and Nmi is likely to be involved in MycN/Nmi interaction in vivo.
Gesehen am 15.02.2019